ANALISIS PELAKSANAAN PROGRAM MERDEKA BELAJAR-KAMPUS MERDEKA DI UNIVERSITAS NEGERI MAKASSAR - Nurwahyuni Palabirani; Farida Febriati; Merissa Monoarfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the independent learing-independent campus program at Makassar State Univercity has problems including obstacles in recognizing grades that are not in accordance with student expectations, as well as the lack of understanding and support from several lecturers for the credit conversion process. This study aims to analiyze the implementation of the independent learning-independent campus program at Makassar State Univercity. The research method used is qualitative with a case study type of research with data collection techniques in the study through observation, in-depth interviews and documentation. Data analysis uses data reduction analysis, data presentation, and drawing conclusions. The techniques used for the validity of the data findings in this study are triangulation and member check. The results of the study show that the implementation of MBKM at Makassar State University has been running optimally, supported by effective socialization. However, the main challenges faced include the lack of clear information regarding the value recognition procedure, the lack of understanding of several lecturers regarding course conversion.